2018
DOI: 10.1172/jci.insight.97011
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral tissues reprogram CD8+ T cells for pathogenicity during graft-versus-host disease

Abstract: Graft-versus-host disease (GVHD) is a life-threatening complication of allogeneic stem cell transplantation induced by the influx of donor-derived effector T cells (TE) into peripheral tissues. Current treatment strategies rely on targeting systemic T cells; however, the precise location and nature of instructions that program TE to become pathogenic and trigger injury are unknown. We therefore used weighted gene coexpression network analysis to construct an unbiased spatial map of TE differentiation during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…In vitro polarized Th17 cells also induce greater acute GVHD of the skin when transferred to allo-HSCT recipient mice ( 50 ), akin to their pathogenic role in other autoimmune and skin inflammatory diseases, such as psoriasis ( 53 ), scleroderma ( 54 ), and lichen planus ( 55 ). In a murine model of acute GVHD where we tracked the evolution of effector T cell gene expression according to time and location, we recently showed that transcriptional profiles of CD8 + effector T cells in the epidermis were highly distinct from other GVHD sites (including the dermis) and did not readily conform to previously published Tc1 or Tc17 signatures ( 35 ). Taken together, these data suggest that there is substantial redundancy in the requirements for acute skin injury in GVHD and/or that the precise molecular mechanisms leading to pathogenicity do not segregate exclusively with the “classic” differentiation pathways.…”
Section: Pathogenic Mechanisms In Skin Gvhdmentioning
confidence: 96%
See 4 more Smart Citations
“…In vitro polarized Th17 cells also induce greater acute GVHD of the skin when transferred to allo-HSCT recipient mice ( 50 ), akin to their pathogenic role in other autoimmune and skin inflammatory diseases, such as psoriasis ( 53 ), scleroderma ( 54 ), and lichen planus ( 55 ). In a murine model of acute GVHD where we tracked the evolution of effector T cell gene expression according to time and location, we recently showed that transcriptional profiles of CD8 + effector T cells in the epidermis were highly distinct from other GVHD sites (including the dermis) and did not readily conform to previously published Tc1 or Tc17 signatures ( 35 ). Taken together, these data suggest that there is substantial redundancy in the requirements for acute skin injury in GVHD and/or that the precise molecular mechanisms leading to pathogenicity do not segregate exclusively with the “classic” differentiation pathways.…”
Section: Pathogenic Mechanisms In Skin Gvhdmentioning
confidence: 96%
“…(B) During acute GVHD, the local production of IFN-γ inducible chemokines in response to tissue injury promotes the recruitment of CXCR3 + alloreactive T cells into the skin ( 34 ). Upon in situ interaction with host-type Langerhans cells, alloreactive T cells are reprogramed to differentiate into pathogenic effector cells characterized by enhanced survival and generation of IFN-γ ( 35 ). Pathogenic T cells kill Lgr5 + epidermal stem cells ( 36 ), thus disabling normal repair mechanisms and epidermopoiesis; these effects are manifested by vacuolar degeneration and apoptosis of the basal and suprabasal epidermal cells, focal dermo-epidermal separation, and necrosis of the epidermis with denudation.…”
Section: Overview Of Gvhd Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations